2012
DOI: 10.1371/journal.pone.0044528
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Dose Distributions in Various Materials from an Ir-192 HDR Brachytherapy Source

Abstract: Dose distributions of 192Ir HDR brachytherapy in phantoms simulating water, bone, lung tissue, water-lung and bone-lung interfaces using the Monte Carlo codes EGS4, FLUKA and MCNP4C are reported. Experiments were designed to gather point dose measurements to verify the Monte Carlo results using Gafchromic film, radiophotoluminescent glass dosimeter, solid water, bone, and lung phantom. The results for radial dose functions and anisotropy functions in solid water phantom were consistent with previously reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Dosimetric measurements of HDR sources in various applicators and catheters have been reported 139,140,143,154,326,332–336 . The effect of phantom material and heterogeneity (applicator/catheters) on the dose distributions can be assessed 142,337,338 . For machine QA, RCFs can be used for checking dwell position accuracy 339–341 and relative dwell times in a catheter or applicator based on the autoradiography method 342 previously employing XV‐2 film.…”
Section: Application Of Rcf Dosimetry In Clinical Radiation Therapymentioning
confidence: 99%
“…Dosimetric measurements of HDR sources in various applicators and catheters have been reported 139,140,143,154,326,332–336 . The effect of phantom material and heterogeneity (applicator/catheters) on the dose distributions can be assessed 142,337,338 . For machine QA, RCFs can be used for checking dwell position accuracy 339–341 and relative dwell times in a catheter or applicator based on the autoradiography method 342 previously employing XV‐2 film.…”
Section: Application Of Rcf Dosimetry In Clinical Radiation Therapymentioning
confidence: 99%
“…These results imply that there are dose distribution differences in water, bone, lung, and inhomogeneous phantoms. It was concluded that clinical parameters do not provide sufficient dose calculation accuracy for different materials, and to improve the brachytherapy treatment quality calculations, TPSs should incorporate material density [ 18 ].…”
Section: Purposementioning
confidence: 99%
“…This is because there are some effects ignored by the TG-43 method such as human tissue densities, material compositions, body interfaces and dose perturbations; due to the use of applicators, these factors have a significant impact on dose distributions in the patient's body. All these effects can be significant in the brachytherapy photon energy range 4,5 and can be included in modern treatment planning systems (TPS) for brachytherapy by using model-based dose calculation algorithms (MBDCAs). The American Association of Physicists in Medicine TG-186 issued guidelines toward implementing TPS, which can take the abovementioned complexities into account.…”
Section: Introductionmentioning
confidence: 99%